Solusi Layak Awal Masalah Transportasi Menggunakan Total Opportunity Cost Matrix-Modified Extemum Difference Method - Fahrudin Muhtarulloh; Sahira Nabila Juliana; Elis Ratna Wulan (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2023)
The transportation problem here is allocating goods from a place (source) to the destination (demand) optimally by considering minimal costs, effective allocation, and scheduling. To get this initial feasible solution using the Total Opportunity Cost Matrix-Modified Extremum Difference Method (TOCM-MEDM) approach. This method is a new method, which begins by making a case into the initial transportation problem table and then converting it into a TOCM (Total Opportunity Cost Matrix) matrix by calculating the difference between rows and columns. Then the entries turn into a TOCM matrix, the next step is to determine the row pointers and column pointers by subtracting the largest value from the smallest value in either row or column. This method is an approach from MEDM (Modified Extremum Difference Method). From these results, it can be continued to determine the maximum pointer cost by looking at the largest pointer. Then just calculate the minimum allocation of each row and column until supply and demand are met. The results of the analysis show that the results of solving the transportation problem to determine the initial feasible solution using the TOCM-MEDM method get the minimum yield costs of 410.